The Ability of Latin Letter Recognition in Early Children in Raudhatul Atfhal Annajamissa'adah Medan Tembung - Abdillah Abdillah; Syaukani Syaukani; Yuni Sitorus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The background of the problem in this study is the ability to recognize Latin letters in early childhood in Raudhatul Atfhal Annajamissa'adah clay field and the teacher has not used an effective and efficient media in learning to recognize Latin letters. This study aims to process learning activities in the form of activities of teachers, students and parents in the ability to recognize Latin letters in early childhood in Raudhatul Atfhal Annajamissa'adah clay field through the process of learning the introduction of Latin letters in early childhood. The results showed that there were some weaknesses and strengths in learning Latin letters recognition. Because children lack enthusiasm in learning because the media conducted by teachers is less effective. Therefore there must be cooperation between parents of students and teachers so that students also study at home not only studying at Raudhatul Atfhal Annajamissa'adah clay field but at home must also be taught by parents so that the ability to recognize Latin letters can die. Because so far researchers see the lack of cooperation between teachers and parents in working together in educating young children in Raudhatul Atfhal Annajamissa'adah so the level of children's ability to recognize Latin letters is different.